FY2018 Armenia Country Opinion Survey Report - World Bank Group (World Bank, Washington, DC, 2019)
The country opinion survey in Armenia assists the World Bank Group (WBG) in gaining a better understanding of how stakeholders in Armenia perceive the WBG. It provides the WBG with systematic feedback from national and local governments, multilateral and bilateral agencies, media, academia, the private sector, and civil society in Armenia on: (1) their views regarding the general environment in Armenia; (2) their overall attitudes toward the WBG in Armenia; (3) overall impressions of the WBG’s effectiveness and results, knowledge work and activities, and communication and information sharing in Armenia; and (4) their perceptions of the WBG’s future role in Armenia.